2020
DOI: 10.1111/jdv.16979
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a deep neural network in teledermatology: a single‐centre prospective diagnostic study

Abstract: Background The use of artificial intelligence (AI) algorithms for the diagnosis of skin diseases has shown promise in experimental settings but has not been yet tested in real‐life conditions. Objective To assess the diagnostic performance and potential clinical utility of a 174‐multiclass AI algorithm in a real‐life telemedicine setting. Methods Prospective, diagnostic accuracy study including consecutive patients who submitted images for teledermatology evaluation. The treating dermatologist chose a single i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 26 publications
4
37
1
Order By: Relevance
“…This conclusion is emphasized by a study completed during COVID-19, where an AI screening tool was used to aid dermatologists in their diagnosis. In this study, AI was shown to be useful in only 11.8% of cases [63]. The significance of these studies combined is that the future of AI lies in aiding clinicians to improve patient care, not in replacing the job of dermatologists altogether.…”
Section: Looking Forward: Teledermatology In a Post-covid-19 Worldmentioning
confidence: 74%
See 1 more Smart Citation
“…This conclusion is emphasized by a study completed during COVID-19, where an AI screening tool was used to aid dermatologists in their diagnosis. In this study, AI was shown to be useful in only 11.8% of cases [63]. The significance of these studies combined is that the future of AI lies in aiding clinicians to improve patient care, not in replacing the job of dermatologists altogether.…”
Section: Looking Forward: Teledermatology In a Post-covid-19 Worldmentioning
confidence: 74%
“…Regardless of the hindrances to telemedicine in the future, technological advances in TD provide a positive outlook on dermatology in a post-COVID-19 world. Recent advancement of AI smartphone applications (apps) allow patients to take photos of skin lesions and receive a speculative diagnosis [63]. A 2020 review of dermatologic AI smartphone apps stated that AI allows skin cancer patients to be treated more effectively and quickly, which is significant given the increasing incidence of skin cancer.…”
Section: Looking Forward: Teledermatology In a Post-covid-19 Worldmentioning
confidence: 99%
“…In another research with 5,014 validated cases, AI obtained 76.9% accuracy in classifying 40 common dermatoses ( 17 ). Further, in a recently conducted study, 340 teledermatology images were tested for 174 different dermatological diseases, obtaining an accuracy of 41.2% ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…This clue was detected by the methods of explainable artificial intelligence (AI) in the context of a human–computer collaboration study 11 . AI‐based decision support may augment human expertise in image‐based diagnostic medicine 14,15 . There are, however, concerns that AI may replace physicians instead of supporting them.…”
Section: Discussionmentioning
confidence: 99%
“… 11 AI‐based decision support may augment human expertise in image‐based diagnostic medicine. 14 , 15 There are, however, concerns that AI may replace physicians instead of supporting them. Instead of playing off human intelligence against artificial intelligence, it might be better to take the best of both worlds.…”
Section: Discussionmentioning
confidence: 99%